Developing Warehouse Employee Performance by Applying the Principles of 7R in Logistics - et. al., Patcharawadee Trichai, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to apply the 7R principles in logistics to develop desirable warehouse employee competencies and to be a guideline for conducting research and development, determining desirable warehouse employee competencies by self-development that means learning the fundamentals of various content with various methods of acquiring knowledge from various sources by themselves or other methods in order to have a better life, better knowledge, work ability and quality of work affected the work results are more efficiency which can classified into 3 areas, namely, self-learning development and further education that mean getting to study in relevant educational institutions and training areas to indicate developing or training for a suitable person or work when considering the relevant facts to mention the important competencies of warehouse employee competencies, namely knowledge, skills, opinions of oneself, personal identity, motivation and attitude.